EFEKTIVITAS FLIPBOOK NANOTEKNOLOGI BERBASIS ETNOSAINS TERINTEGRASI AUGMENTED REALITY DALAM MENDUKUNG PROGRAM SDGs UNTUK SISWA SMA - Ezha, Sephianti Dwika; Nurjanah, Desi Fauza; Amalia, Vina Nurul; Ramaulita, Thara Nabila; Nursyahbana, Galih Lazuardi; Rohman, Ijang; Suhanda, Hokcu; Rahmawati, Triannisa (UIN AR-RANIRY, 2024)
A flipbook with augmented reality based on ethnoscience, supported by Heyzine and Assembler, contains nanotechnology content for high school students. It is an interactive learning media in the form of an electronic book that contains photos, text, and animated content designed to assist students in learning the material through the visuals offered. Page flipping has a transition effect that helps students read each page and increases their learning use. Applied visual arts ethnoscience exemplifies the combination of community culture and science. Augmented reality is utilized to show objects in 3D and realistically related to the ethnoscience of applied fine arts in the Cirebon area, such as the scissor-grip home, megamendung batik, ceramics, masks, kujang, and paintings. The goal of this research is to develop digital teaching materials that can adjust to evolving technologies in order to increase educational quality. The data was collected using a quasi-experimental one-group pretest-posttest design for a total of 30 students, which was then processed using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) using descriptive statistics. This study found that students had good perceptions of the presence of a flipbook media with AR based on ethnoscience. Ethnoscience-based digital learning media can be used as interactive learning media because they provide precise visualizations of the concepts and conditions encountered during the learning process.